Mob justice and 'The civilized commodity'. Issue 4 (7th June 2021) - Neimark, Benjamin; Osterhoudt, Sarah; Blum, Lloyd; Healy, Timothy
ABSTRACT: Our theory of 'the civilized commodity' examines 'mob violence' affecting high-value commodities, including the vanilla boom of Madagascar. We illustrate producers' labor under fraught conditions of violence and contradictory claims of 'street justice.' Specifically we ask, what counts as justice and to whom? We highlights broader arguments around 'moral hyper-proximity' of producer-consumer relations, and the strategies of state and market actors to circulate 'civilized' visions for systemic and future governance over commodity landscapes. State and market calls for 'law and order, ' however, obscure the structural inequities faced by smallholders in their 'everyday' production of commodities under periodic crisis.